An Analysis of Moral Competency Emphasis in Grade 10 Edukasyon Sa Pagpapakatao at Cabuyao Integrated National High School - Mary Jane Arrieta (Journal of Arts, Humanities and Social Science)
This research examined the focus on moral competency in Grade 10 Edukasyon sa Pagpapakatao (EsP) curriculum as perceived by students. Using a quantitative method, the study surveyed 150 Grade 10 students from Cabuyao Integrated National High School. A guided questionnaire, aligned with the Most Essential Learning Competencies (MELCs) of the Department of Education was used to measure students' self-reported understanding and internalization of key moral concepts such as freedom, conscience, dignity, and patriotism.  Descriptive statistics and Pearson correlation on data analysis found that while all moral competencies received moderate emphasis, freedom and conscience received greater emphasis, whereas patriotism and environmental stewardship were less emphasized. There was a significant correlation between students' self-reported use in actual situations and the perceived focus on moral values (r = 0.63, p < 0.01). The findings highlight the need to strengthen the underemphasized competencies and provide equitable curricular delivery. This research contributes to understanding the effectiveness of values education in developing morally responsible citizens and suggests practical solutions for improving EsP pedagogical practices.